Proviral insights of glycolytic enolase in Bamboo mosaic virus replication associated with chloroplasts and mitochondria - Kuan-Yu Lin; Ying-Wen Huang; Liang-Yu Hou; Hsin-Chuan Chen; Yu Wu; I-Hsuan Chen; Ying-Ping Huang; Shu-Chuan Lee; Chung-Chi Hu; Ching-Hsiu Tsai; Yau-Heiu Hsu; Na-Sheng Lin (Proceedings of the National Academy of Sciences, 2025)
Diverse single-stranded RNA viruses employ different host cellular organelles or membrane systems to compartmentalize their replication intermediates and proviral factors, ensuring robust replication. Replication of Bamboo mosaic virus (BaMV), an Alphaflexiviridae family, is tightly associated with chloroplasts and dynamic cytosolic viral replication complex (VRC) clusters. BaMV VRC clusters comprise double-stranded viral RNA, BaMV replicase (Rep BaMV ), and mitochondrial outer membrane protein, voltage-dependent anion channel (VDAC). In this study, we demonstrate that host glycolytic enolase (ENO) binds to untranslated regions of BaMV RNA independently of ENO hydrolytic activity. However, the structural integrity of ENO is essential for its direct interaction with Rep BaMV , and its positive regulating role in BaMV replication and the size of BaMV VRC clusters. Additionally, ENO, pyruvate kinase (PYK), and VDAC colocalize within cytosolic BaMV VRC clusters embedded in the convoluted endomembrane reticulum (ER) along with ER-targeted viral movement proteins under BaMV infection. This association suggests that the ENO-PYK-VDAC metabolon, with ENO serving as a scaffold to link chloroplasts and mitochondria, may play a pivotal role in BaMV robust replication. Collectively, our findings offer significant insights into how glycolytic ENO acts in BaMV replication.